The pedigree registration of European bison as a tool in the restitution of the species (European Bison Conservation Newsletter, 2013)
The extinction of the last wild population of European bison in Poland’s Białowieża Forest in 1919 became stimulus for an action to restitute the species, leading to the establishment in Berlin in 1923 of the International Society for the Protection of the European Bison (Internationale Gesellschaft zur Erhaltung des Wisents). This body’s first task was the drawing up of a census-based inventory, followed later by fuller registration of the European bison being held in captivity at this time. This was the beginning of European Bison Pedigree Book. The first edition of the Pedigree Book, covering the years 1931–1936, was the work in Germany of Goerd von der Groeben and Erna Mohr. However, when the Second World War ended, it was to Poland that responsibility for publishing the book passed, Dr Jan Żabiński being given charge of the work in 1947. European Bison Pedigree Book (EBPB) has since assumed the task of annual registration of all European bison alive in the world. Animals kept in captivityin enclosures are noted as individuals, and assigned pedigree numbers by the Editorial Office of the EBPB. For obvious reasons, the breeding centres maintaining free-ranging populations may only be registered in line with the size of the population at the end of each year. Registration proceeds in parallel for two breeding lines – that of the Lowland (Białowieża) line and that of the Lowland-Caucasian line, the latter descending from the bull No.100 Kaukasus – the single surviving individual of the Caucasian bison subspecies. The number of centers engaging in enclosure-based breeding (breeding centres, zoos and show reserves/enclosures) increased steadily up to the mid-1980s, but has since stabilized. In 2011, the centers kept a total of 1552 European bison. In turn, the numbers of European bison at centers where animals are free-ranging or semi-free-ranging also increased up to the first half of the 1990s, and the years since 2011 have again brought an upward trend. As of 2011, there were 3111 wild bison, this representing 66.7% of the world herd. Institutions existing alongside the EBPB include, at Warsaw University of Life Sciences (SGGW), the European Bison Conservation Center (EBCC) and the European Bison Advisory Center (EBAC). Both of these units draw on pedigree information as they seek to limit inbreeding in the world herd through genetic-based assessments of which animals should be bred with. Pedigree breeding of bison in enclosures combined with the growing free-ranging herds in Central and Eastern Europe allowed to ensure that there were 4663 bison in all categories as of 2011, with every chance of the world population growing further, while also improving qualitatively in genetic terms.
Keywords: European bison; restitution of the species; world population; captive breeding; free ranging herds